2015
DOI: 10.1128/ec.00239-14
|View full text |Cite
|
Sign up to set email alerts
|

The Selenocysteine tRNA Gene in Leishmania major Is Transcribed by both RNA Polymerase II and RNA Polymerase III

Abstract: dEukaryotic tRNAs, transcribed by RNA polymerase III (Pol III), contain boxes A and B as internal promoter elements. One exception is the selenocysteine (Sec) tRNA (tRNA-Sec), whose transcription is directed by an internal box B and three extragenic sequences in vertebrates. Here we report on the transcriptional analysis of the tRNA-Sec gene in the protozoan parasite Leishmania major. This organism has unusual mechanisms of gene expression, including Pol II polycistronic transcription and maturation of mRNAs b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The three eukaryotic RNA polymerases are specific for their own promoters, though some exceptions have been found where more than one polymerase can use the same promoter (James Faresse et al 2012; Duttke 2014; Padilla-Mejia et al 2015). Using specific enzyme inhibitors in human cells and extracts (Seidl et al 2013), we previously found evidence of coligo transcription exclusively by Pol III.…”
Section: Resultsmentioning
confidence: 99%
“…The three eukaryotic RNA polymerases are specific for their own promoters, though some exceptions have been found where more than one polymerase can use the same promoter (James Faresse et al 2012; Duttke 2014; Padilla-Mejia et al 2015). Using specific enzyme inhibitors in human cells and extracts (Seidl et al 2013), we previously found evidence of coligo transcription exclusively by Pol III.…”
Section: Resultsmentioning
confidence: 99%
“…These assays were performed as described before [30, 36] with isolated nuclei from 2 × 10 8 mid-log promastigotes. Labeled nascent RNA was hybridized to Hybond-N+ membranes (GE Healthcare) containing dots of 2 μ g of plasmid DNA.…”
Section: Methodsmentioning
confidence: 99%
“…These experiments were performed as described elsewhere (Martinez-Calvillo et al 2003;Padilla-Mejia et al 2015), with nuclei isolated from 2 × 10 8 mid-log cells incubated for 48 h in the presence of doxycycline. Labelled nascent RNA was hybridized to Hybond filters (Amersham) containing dots of 2 µg of plasmid DNA.…”
Section: Nuclear Run-on Experimentsmentioning
confidence: 99%